Environmental Accounting from an Islamic Quadruple Bottom Line Perspective For Environmental Sustainability - Nikmatul Masruroh; Lailatul Farha; Ahmad Fadli; Zhainar Zhabatayeva (IAIN Syekh Nurjati Cirebon, 2025)
This study explores the application of environmental accounting within the Islamic Quadruple Bottom Line (QBL) framework to promote environmental sustainability. Utilizing a qualitative case study approach at PT. Sinergi Gula Nusantara, a sugar factory in Indonesia, this research examines how the company identifies, recognizes, measures, presents, and discloses environmental costs. The analysis integrates the QBL dimensions—profit, people, planet, and purpose—with Islamic prophetic values (nubuwwah), namely shidddiq (truthfulness), amanah (trustworthiness), tabligh (advocacy), and fathonah (wisdom). Findings revealead that the company implements various environmental cost management practices, from waste prevention to pollution control. When viewed through the Islamic QBL lens, these practices not only aim for economic efficiency (profit) but also demonstrate commitment to social welfare (people) and ecological preservation (planet). The internalization of nubuwwah values provides a spiritual and ethical foundation (purpose) for corporate environmental responsibility. This study contributes a novel framework for analyzing and implementing environmental accounting in a manner that harmonizes economic objectives with social, environmental, and spiritual goals, offering a culturally relevant model for corporations in Muslim-majority regions.